(untitled) (Eurasian Journal of Philology Science and Education, 2018)
In article the strategy of analytical reading works of I. Shehegolikhin in higher education institution are considered. The author claims that analytical reading should be based on the system of heuristic questions and tasks on studying of creativity of I. Shehegolikhin. In the course of studying of literary works it is also recommended to apply to deepening of reading and activization of thinking special forms of the organization of thought process: drawing up mental maps by students and method of «brainstorming» (brainstorming). The method of «brainstorming» is intended for producing the ideas or decisions during the work in group. Analytical reading art texts gives to students the chance to feel in the course of coauthorship with the author